2013
DOI: 10.1017/neu.2013.55
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of facial affect recognition in children and adolescents with attention-deficit/hyperactivity disorder under methylphenidate

Abstract: The collected data showed that methylphenidate leads to amelioration of facial affect recognition abilities, but not on a significant level. Reasons for missing significance may be the small sample size or the fact that there exists some overlapping in cerebral connections and metabolic pathways of the site of action of methylphenidate and the affected dopaminergic areas in ADHD. However, consistent with the endophenotype concept, certain gene locations of the dopaminergic metabolism as both an aetiological fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Seven studies [ 31 , 50 , 58 , 60 , 68 , 69 , 70 ] assessing the effects of psychostimulants and nonstimulant drugs on emotion recognition abilities in individuals with ADHD were finally identified. Most of the studies were conducted on children and adolescents aged 7 to 17 years old, except for one study [ 69 ] that included adult patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven studies [ 31 , 50 , 58 , 60 , 68 , 69 , 70 ] assessing the effects of psychostimulants and nonstimulant drugs on emotion recognition abilities in individuals with ADHD were finally identified. Most of the studies were conducted on children and adolescents aged 7 to 17 years old, except for one study [ 69 ] that included adult patients.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies were conducted on children and adolescents aged 7 to 17 years old, except for one study [ 69 ] that included adult patients. Diagnoses were based on DSM-IV and, in one case [ 31 ], on the ICD classification system, and included different proportions of ADHD subtypes; intelligence was generally on average, whereas other psychiatric comorbidities were excluded based on standardized criteria except for two studies [ 50 , 68 ] that included learning disabilities and internalizing disorders, respectively. Further details of the studies are reported in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a deficiency in recognizing emotions from facial expressions in children and adolescents with ADHD (Yuill and Lyon 2007). In some studies, recognizing emotions from facial expressions was also found to improve with methylphenidate treatment (von Morgenstern et al 2014). Therapies focusing on emotional skills such Psikiyatride Güncel Yaklaşımlar -Current Approaches in Psychiatry as emotion management is reported to be effective for various psychiatric disorders, including ADHD (Mennin and Farach 2007).…”
Section: Treatmentmentioning
confidence: 99%